Microbiological monitoring of the rivers Achariskali and the Bartskhana in Western Georgia - Mirangula Liparteliani; Tea Mchedluri; Ketevan Dolidze (Web of Journals Publishing, 2023)
Among the problems arising in the field of environmental protection in Georgia, the issue of river pollution stands out. They are mostly polluted by agricultural, industrial and household waste and direct human activities. The growing anthropogenic load on the rivers can lead to the breakdown of the balance of substances in the water ecosystem, the deterioration of the sanitary-hygienic and recreational conditions of the water body, and finally the degradation of water body resources. Preservation and protection of the desired ecological condition of rivers require a special approach and solution. It is necessary to constantly monitor them in order to determine the source of pollution and the ways of its spread. In order to evaluate the degree of pollution caused by anthropogenic factors, we conducted sanitary-microbiological studies in 2019, 2020 and 2021 on two rivers of Western Georgia (the Bartskhana and the Ajgaritstskali). In the analysis samples, we determined sanitary-microbiological indicators - total coliforms, Escherichia coli, fecal coliforms, Salmonella. Based on the results of the research, we can conclude that microbial pollution was observed in the Adjaristskali in the summer and autumn of 2019. The increase of anthropogenic load in the river Bartskhana is observed in all three years, which, in our opinion, is caused by agricultural and household pollution. The mentioned problem requires a serious approach and decisive measures.
Keywords: anthropogenic pollution, total coliforms, Escherichia coli, faecal streptococci, Salmonella.